IMPROVING ORGANIZATIONAL DEVELOPMENT OF CONSTRUCTION MANAGEMENT - Mukhtasar Karimova Israiljon qizi (Journals Park Publishing, 2022)
Building production has an interbranch characteristic and takes into account the cooperation of different partners. Rationalization of building production management methods is impossible without searching for more effective forms of management of promotion of production to the final customer, optimal organization building of production and technological systems and development of economic mechanism of division of results of interaction.
Keywords: Construction, management, production, technological systems, modern, continuous provision.